IMPLEMENTASI DOKUMEN PELAKSANAAN ANGGARAN SEBAGAI BAGIAN LAPORAN PERTANGGUNGJAWABAN PADA AKUNTABILITAS PUBLIK DAN TRANSPARANSI - Suteja, I Made Agus; Budiasih, I.G.A. Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.01.TAHUN 2016, 2016)
There are two goals in this research. The first goal is to know the effect of implementing budget realization document toward public accountability and the second goal is to know the effect of implementing budget realization document toward transparency. Purposive sampling was chosen as the sampling method and 53 local government work units were used as sample. The result of the discussion shows that implementing the budget realization document gives positive effect to public accountability and transparency.  The more increasing public accountability will make budget realization document improve on the same way. In addition, the more increasing the transparency also will make budget realization document improve as well. Government accounting standard is used as the basis of accountability report. It is due to the reason that government accounting standard is a tool to facilitate the report for the improvement of public accountability and transparency.
Keywords: Implementation of budget realization document, Public accountability, Transparency